Construction of educational technology for self care in heart failure (Research, Society and Development, 2020)
The aim of the study was to build a digital educational technology to guide self-care to heart failure patients and their caregivers. Therefore, the methodology consists of two stages: 1) Integrative Literature Review; 2) Elaboration of educational technology using the instrument called “Plain-Language Checklist for Creating and Reviewing Your Materials / 2013”. As a result of the Review, the following categories were highlighted: self-care as a hindrance, the impact of caregivers on quality of life, coping/focused coping, literacy, mood disorders, fatigue and dyspnea. Strategies and guidelines for addressing these difficulties were included in the technology created, which resulted in 41 pages. Finally, it is concluded that patients with heart failure and their caregivers need information about the pathology, once this can increase the quality of life, decrease exacerbation and rehospitalizations. During the Corona virus pandemic, it is believed that the technology created may assist in the management of self-care, avoiding unnecessary exposure to health services or alerting to clinical manifestations that deserve face-to-face assistance, avoiding the fear of acquiring COVID-19 in a hospital is an obstacle for decompensated patients to seek care.